THE ROLE OF RIGID BRONCHOSCOPY IN CHILDREN WITH TRACHEOBRONCHIAL FOREIGN BODY ASPIRATION - TARAR, JM; BHATTI, S; RASHID, M (Biological and Clinical Sciences Research Journal, 2022)
To assess the role of rigid bronchoscopy in children with tracheobronchial foreign body aspiration (FBA) a retrospective study was carried out in Pediatrics Ward of Bakhtawar Amin Trust Hospital & Medical & Dental College Multan for 1 year. A total of 80 children aged 6 months to 15 years with foreign body aspiration were included in the study. Data was collected from the medical histories of the patients. Rigid bronchoscopy was performed in all patients under anesthesia. All the data was analyzed by using SPSS version 21. The study was conducted on total 80 patients whose mean age was 2.5 years. 66 (82.5%) patients aspirated organic FBs, while 14 (17.5%) aspirated inorganic FBs. Cyanosis (37,46.2%) and stridor (33,41.2%) were the most common symptoms. In 78 (97.5%) patients rigid bronchoscopy was performed. In 75 (93.7%) not post operative event occurred. Medical history of patients with FBA is important for diagnosis. In addition, bronchoscopy is mandatory in patients with history of choking even if chest x-ray and initial examination are normal.